E-Commerce Fraud Perceptions in Pakistan and Impacts of Risks and Preventive Measures - Ahmad, Faraz; Simpao, Kristine Joy (Yayasan Mitra Peduli Indonesia, 2025)
This study delves into the perceptions of e-commerce fraud in Pakistan by assessing the risks and preventive measures against such fraudulent activities. Employing a robust methodology that encompasses surveying a diverse group of stakeholders in the Pakistani e-commerce sector, this study scrutinizes their perspectives and experiences. The findings reveal a heightened concern regarding fraudulent practices, significantly challenging the industry's integrity and consumer trust. This concern is exacerbated by the rapid growth of e-commerce, making fraud prevention a critical issue. The study's statistical analysis sheds light on the prevalent types of fraud and their impact on consumers and businesses and evaluates the effectiveness of current prevention strategies. This conclusion draws attention to the need for more robust, multifaceted approaches to combat e-commerce fraud. Recommendations have been proposed to enhance fraud detection and prevention mechanisms. These include adopting advanced technological solutions, increasing consumer awareness, and implementing strict regulatory measures.